Podemos and the New Political Cycle Left-Wing Populism and Anti-Establishment Politics (Springer International Publishing, 2018)
This edited volume explores the context in which the Spanish party Podemos operates as both an agent and product of political cycles. It provides an account of the party's genealogy, ideological environment and relation to other political initiatives in Latin America and Western Europe. The contributors address the multiples dynamics generated by Podemos as a new party developed out of the economic crisis, the structural crisis concerning social democracy and the incarnation of the welfare state project, and, more generally, out of the Left. It will appeal to upper-level students and scholars interested in Spanish politics, history, culture and sociology.